2010
DOI: 10.1182/blood-2009-11-256610
|View full text |Cite
|
Sign up to set email alerts
|

Activated protein C cofactor function of protein S: a critical role for Asp95 in the EGF1-like domain

Abstract: Protein S has an established role in the protein C anticoagulant pathway, where it enhances the factor Va (FVa) and factor VIIIa (FVIIIa) inactivating property of activated protein C (APC). Despite its physiological role and clinical importance, the molecular basis of its action is not fully understood. To clarify the mechanism of the protein S interaction with APC, we have constructed and expressed a library of composite or point variants of human protein S, with residue substitutions introduced into the Gla,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(60 citation statements)
references
References 43 publications
3
57
0
Order By: Relevance
“…26,27 Only protein S Gla variants previously shown to bind normally to phospholipid membranes were evaluated for their TFPI cofactor function. 27,28 In addition, the cDNA for 3 previously described protein S/Gas6 chimeras were available.…”
Section: Generation and Expression Of Protein S Variantsmentioning
confidence: 99%
See 3 more Smart Citations
“…26,27 Only protein S Gla variants previously shown to bind normally to phospholipid membranes were evaluated for their TFPI cofactor function. 27,28 In addition, the cDNA for 3 previously described protein S/Gas6 chimeras were available.…”
Section: Generation and Expression Of Protein S Variantsmentioning
confidence: 99%
“…26,27 Protein S purification and quantification WT protein S and protein S variants were either concentrated in conditioned medium or purified using barium citrate precipitation 29 followed by anionexchange chromatography as previously described. 27 Protein S concentrations of WT protein S and protein S single or composite variants (spanning Gla-TSR-EGF1-EGF2-EGF3-EGF4) were determined by a previously described in-house enzyme-linked immunosorbent assay (ELISA).…”
Section: Generation and Expression Of Protein S Variantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on modeling of the tertiary structure of the EGF‐2 domain of PS, Lys 196 is on the surface of the molecule,4 where it likely interacts with APC. The functional importance of Lys 196 was previously reported by an Ala replacement study, where the K196A variant showed modestly reduced APC cofactor activity 22. We have previously obtained monoclonal antibodies specific to the PS‐E in the native form, indicating the surface presentation of the Lys 196 residue 23…”
Section: Resultsmentioning
confidence: 55%